Atividades biológicas de pterocaulon angustifolium, praxelis sanctopaulsensis e disynaphia filifolia e avaliação da ação conservante em emulsões - Battistella, Alana Carla (2020)
The use of vegetal extracts by man is common since the most remote times and nowadays some of its antimicrobial and antioxidant properties are explored scientifically and can be used in pharmaceutical, cosmetic, agricultural, and food formulations. The objective of this study was to evaluate the antimicrobial and antioxidant activity of extracts and fractions of Pterocaulon angustifolium, Praxelis sanctopaulsensis and Disynaphia filifolia and to verify the conservative faction of the diclorometano fraction of P. angustifolium in emulsions for stability studies. The raw extracts were prepared with ethanol by the maceration process. Then, fractionation by partition was performed using hexane, dichloromethane, butanol, ethyl acetate, butanol, methanol and water. For the determination of the antimicrobial activity the technique of determining the Minimum Inhibitory Concentration (MIC) and Minimum Bacterial Concentration (MBC) was used using Gram positive bacteria (Bacillus subtilis, Bacillus cereus and Staphylococcus aureus) and Gram negative bacteria (Escherichia coli, Pseudomonas aeruginosa, Salmonella enterica, Shigella flexnerii and Klebsiella pneumoniae). A bacterial time of death study was performed for B. subtilis, B. cereus, S. aureus, P. aeruginosa and S. flexnerii using the dichloromethane fraction of P. angustifolium (PA-DCM). In the evaluation of the antioxidant profile, DPPH (2,2-diphenyl-1-picryl-hydrazyl) and FRAP (iron reduction antioxidant power) methods were performed. To evaluate the preservative action of PA-DCM in emulsions five formulations were developed: F1 (control), F2 (with 0.5% of PA-DCM), F3 (with antioxidants and synthetic antimicrobials), F4 (with 0.5% of PA-DCM and synthetic antioxidants) and F5 (with synthetic antimicrobials and 0.05% of PA-DCM) which were submitted to preliminary and accelerated stability tests for 28 days. Regarding the results of CIM and CBM it was observed that the dichloromethane fraction of P. angustifolium presented greater relevance inhibiting the growth of B. subtilis, B. cereus, S. aureus, P. aeruginosa and S. flexnerii and with bactericidal action against them, except for B. cereus which showed only bacteriostatic action. These results were confirmed in the evaluation of the time death curve of microorganisms. In the evaluation of the antioxidant activity using the DPPH technique, the ethyl acetate fraction of P. angustifolium stood out and showed a result of 1127.78 µmol ET g1, while for FRAP, the ethyl acetate fraction of P. sanctopaulsensis showed activity of 1704.296 µmol ET g -1. For the dichloromethane fraction of P. angustifolium the result in the DPPH method was 1001.11 µmol ET g-1 and in the FRAP method it was 339.56 µmol ET g-1. PADCM was used in the development of emulsions, which were exposed to preliminary stability and presented results of appearance, color, odor, microscopy, pH and conductivity unchanged, as well as no phase separation after centrifugation of the samples. The emulsions were then exposed to accelerated stability and were stable for 28 days at temperatures of 25°C and 45°C in analyses of appearance, color, odor, microscopy, pH, conductivity, acidity index, DPPH, particle size, microbiological analyses and fatty acids. Also, it was observed that PA-DCM significantly prevented microbial proliferation in emulsions. Thus, it is concluded that PADCM consists of a natural product that presents antimicrobial and antioxidant activity, as well as demonstrates preservative action when applied in emulsion type formulations, which can be used in pharmaceutical, agricultural, cosmetic and food areas.